2005
DOI: 10.1124/jpet.105.089607
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of Activating Transcription Factor 3 Involves the Early Growth Response-1 Gene

Abstract: Previously, our laboratory identified activating transcription factor 3 (ATF3) as up-regulated by nonsteroidal anti-inflammatory drugs using microarray analysis of mRNA from human colorectal cancer cells treated with sulindac sulfide. ATF3 is a transcription factor involved in cell growth, apoptosis, and invasion and is induced by a variety of anticancer and dietary compounds. However, the regulation of ATF3 by anticancer agents is not known. The promoter of ATF3 contains several transcription factor binding s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…As a further proof, we showed that the selective activation of the ERK signaling pathway in HaCaT cells expressing a conditionally active form of A-Raf protein kinase induced expression of the zinc finger protein Egr-1 but not expression of ATF3. Egr-1 has been shown to transactivate the ATF3 gene in sulindac sulfideor troglitazone-treated human colorectal cancer cells or GnRHstimulated gonadotrophs (Bottone et al, 2005, Mayer et al, 2008a. The results presented here showed that Egr-1 plays no role in the thapsigargin-stimulated up-regulation of ATF3 in HaCaT keratinocytes.…”
Section: Thapsigargin-induced Signaling In Keratinocytes 873mentioning
confidence: 38%
“…As a further proof, we showed that the selective activation of the ERK signaling pathway in HaCaT cells expressing a conditionally active form of A-Raf protein kinase induced expression of the zinc finger protein Egr-1 but not expression of ATF3. Egr-1 has been shown to transactivate the ATF3 gene in sulindac sulfideor troglitazone-treated human colorectal cancer cells or GnRHstimulated gonadotrophs (Bottone et al, 2005, Mayer et al, 2008a. The results presented here showed that Egr-1 plays no role in the thapsigargin-stimulated up-regulation of ATF3 in HaCaT keratinocytes.…”
Section: Thapsigargin-induced Signaling In Keratinocytes 873mentioning
confidence: 38%
“…This molecule belongs to the ATF3/CREB transcription factor family [4], which is described as a tumour suppressor. Additionally, we detected an upregulation of EGR1, another transcription factor and immediate early gene belonging to the EGR family of C 2 H 2 -type zinc-finger proteins, which is discussed to be necessary for the induction of ATF3 [21]. …”
Section: Discussionmentioning
confidence: 99%
“…Intestinal epithelial injury activates these protective PKR-ERK1/2 signals, leading to induction of target genes, such as early growth response gene 1 involved in the regeneration process (49,50). NSAIDs enhance early growth response gene 1 expression via ERK1/2 signaling pathway, which attenuates NSAID-induced epithelial cytotoxicity (51,52). In the current study, NAG-1 also played protective roles against ulcerative injuries by promoting epithelial restitution.…”
Section: Discussionmentioning
confidence: 99%